THE ASSOCIATION OF EATING HABITS AND CONSUMPTION OF FOOD FROM OUTSIDE THE HOSPITAL WITH FOOD WASTE OF CLASS III INPATIENTS AT HOSPITAL X IN KARAWANG REGION - Fiqma, Diana; Elvandari, Millyantri; Andriani, Eka (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2026)
The Minimum Hospital Service Standards state that the remaining food that is not eaten by patients is <20%, which is an indicator of the success of nutrition services in every hospital in Indonesia. This study aims to analyze the relationship between eating habits and consumption of food from outside the hospital with the remaining food of inpatients at Karawang Regional Hospital. This research design uses observational type and with cross sectional research. Samples were selected using purposive sampling method with a total of 109 respondents. Data collection was carried out by measuring the rest of the patient's meal and using a questionnaire. The results of this study showed that most patients were >45 years old, 58.7% female, and dominated by the last education of SPM patients 43.1%. Based on the category of frequency of eating habits that are high or frequent 57.8%, as many as 72.5% of patients consume food from outside the hospital, and 63.3% of patients have a lot of food waste or >20%. There was a significant relationship between eating habits and food waste (p=0.019). There is a significant relationship between consumption of food from outside the hospital and food waste (p=0.008).